Kedudukan Alat Bukti Elektronik Dalam Pembuktian Tindak Pidana - Ilham, Ade Ihwana; Shuhufi, Muhammad; Amin, Abd. Rauf Muhammad (Media Hukum Indonesia (MHI), 2024)
This research aims to determine and analyze the status of electronic evidence, especially in criminal acts. This journal writing method uses a normative legal method using a statutory approach and a conceptual approach. The results of the study show that the position of electronic evidence is an expansion of documentary evidence and instructions based on 184 of the Criminal Procedure Code. Even though the Criminal Procedure Code does not regulate the lex generalis, for the sake of creating substantial truth, electronic evidence guidance tools can be used as valid evidence in criminal trials. In criminal procedural law there is no hierarchy of evidence. However, in its development, electronic evidence must be considered in making clear a criminal case.